Monocyte Correlates of Neurocognitive Impairment in Chronic HIV infection, Early, Persistent Changes with Antiretroviral Therapy - Hai Duc Nguyen; Andrew K. Ding-Su; Caroline Soulas; Tricia H. Burdo; Patrick Autissier; Pasiri Sithinamsuwan; Nitiya Chomchey; Jintanat Ananworanich; Victor Valcour; Silvia Ratto-Kim; Woong-Ki Kim; Kenneth C. Williams (JCI Insight, 2026)
Rationale: Persistent monocyte activation contributes to HIV-associated neurocognitive disorders (HAND), yet biomarkers that predict neurocognitive impairment before and after antiretroviral therapy (ART) remain incompletely defined. Objectives: We evaluated monocyte subsets and activation markers in participants from the SEARCH007 cohort prior to ART initiation and at 6 and 12 months following treatment. Methods and Results: Increased frequencies of CD14+CD16+ monocytes and elevated CD163 expression were associated with worsening neurocognitive performance and HAND severity. Plasma soluble CD163 levels increased with neurocognitive impairment and correlated with plasma HIV RNA levels, while CCR2 expression was associated with NPZ Global scores. Notably, CD169 expression was elevated across all monocyte subsets and demonstrated a stepwise increase with worsening neurocognitive impairment. Although ART reduced overall monocyte activation, elevated CD169 expression persisted in some individuals despite virologic suppression. Bayesian kernel machine regression and random forest analyses identified CD169 expression as one of the strongest predictors of cognitive impairment, surpassing plasma viral load, CD4+ T-cell count, and several established monocyte activation markers. Conclusions: These findings identify monocyte CD169 expression as a biomarker of neurocognitive dysfunction before and during the first year of ART and support further investigation of its role in HAND pathogenesis.